When silence isn't golden: The key role of communication during crisis situations. Issue 12 (9th December 2019) - Unknown
Abstract : Purpose: This paper aims to review the latest management developments across the globe and pinpoint practical implications from cutting-edge research and case studies. Design/methodology/approach: This briefing is prepared by an independent writer who adds their own impartial comments and places the articles in context. Findings: Organizations should utilize social media platforms like Twitter to communicate effectively with stakeholders impacted in the wake of a preventable corporate crisis. It is critical to deploy relevant communication strategies in order to repair relations and minimize damage caused to the reputation and legitimacy of the firm. Originality/value: The briefing saves busy executives and researchers hours of reading time by selecting only the very best, most pertinent information and presenting it in a condensed and easy-to-digest format.